Advances in Tribology - Darji, Pranav H. (IntechOpen, 2016)
In the major field of design and manufacturing of mechanical, production, automobile, and industrial engineering, typical and advance methodologies and processes are implemented for the best performance of product or machinery. Thus, the concept of tribology has come into practice for even better performance. Nowadays, it is very important that the tribological knowledge be implemented at each stage of design and manufacturing to minimize the frictional and wear losses, and ultimately these will serve as best preference for the economical growth of the nation. Currently, tribologists are playing vital role in the same direction. This book contains original and innovative research studies on recent applications of tribology, contributed by the group of selected researchers describing the best of their work. Through its 11 chapters, the reader will have access to work in 3 major areas of tribology. These are surface engineering and coating, friction and wear mechanism, and lubrication technology. The first part of the book from Chapters 1 to 4 deals with the surface treatment and coating through which component life can be improved by reducing wear rate. The second part of the book from Chapters 5 to 7 deals with tribo-testing and tribo-system monitoring for friction and wear mechanism presented with real-life case studies. The third part from Chapters 8 to 11 discusses the advances in lubrication, which also includes the role of nanolubricants and lubrication additives. This book may be of interest to research scholars, academicians, industrialists, professional engineers, and specialists in these related areas and would also be of immense help to various practicing engineers, technologists, managers, and supervisors engaged in the maintenance, operation, and upkeep of different machines, equipments, systems, and plants of various industries.